TENCEL®with a Microbial Barrier for Medical Bras (Journal of Fiber Bioengineering and Informatics, 2015)
The goal of the research was to determine the properties of the microbial barrier TENCEL\u00ae knittedfabrics intended for medical bras. The samples were tested according to a new method developed inthe earlier research by the same authors. The most resistant forms of microorganisms of a pathogenicbacterial endospore of the Bacilllus genus were used to investigate microbial barrier permeability. Basedon the samples tested and their characteristics, medical bra construction was developed with the aim ofreducing irritation for the body part that underwent surgery. The data on the forms and measures wereobtained using a 3D body scanner.